OPTIMIZATION OF PAVEMENT STRUCTURES AT AIRPORT BASED ON VARIATIONS IN AIRCRAFT TRAFFIC (CASE STUDY : DOMINE EDUARD OSOK AIRPORT) - Nur Ajizah, Rahmah
As the frequency of flights from Domine Eduard Osok Airport increases, a runway is planned that is able to withstand the weight of aircraft repittion when the aircraft operates. By optimizing the runway pavement structure based on variations in aircraft traffic. The purpose of the research to be achieved in this study is to determine the contribution of each pavement layer to the value of Pavement Classification Number (PCN) and Cumulative Damage Factor (CDF). This research was conducted for variations in aircraft traffic, namely mix traffic, wide body and narrow body. Identification is also carried out to determine the impact on runway pavement that occurs due to aircraft repittion loads. In this study, the type of pavement chosen was flexible pavement and the method used was the FAA (Federal Administration Aviation) method. In pavement structure optimization using FAARFIELD and COMFAA programs. The result of this planning with the addition of an overlay on the existing runway pavement has an impact on increasing the value of the existing runway PCN, which was originally 44 F/C/X/T increased to mix traffic modulation of 85 F/C/X/T, narrow body modulation of 62 F/C/X/T and wide body modulation of 82 F/C/X/T. These results make the airport runway able to accommodate medium and large aircraft and the pavement structure is able to accept the planned aircraft repitation load that will be served by the Domine Eduard Osok Airport runway.